The Relationship between Leadership Styles and Team Cohesion of Amhara League Volleyball Players; In Ethiopia - Birhanu, Gizachew (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2023)
Leadership styles have a different effect on the cohesion level of players. Therefore the purpose of this study was to examine the relationship between leadership styles and team cohesion of Amhara league volleyball players, Ethiopia. The study employed 11 volleyball teams (N = 124) that participated in Amhara league volleyball competition. Therefore, participants were selected by using comprehensive sampling methods so that all volleyball players in the 11 Amhara league teams were samples of the study. Each athlete completed, a Group environment questionnaire, to measure team cohesion, and a leadership scale for sport for leadership style. Data were analyzed by using descriptive statistics Mean and standard deviation, and Pearson correlation and the result showed that training and instruction style was the player’s most perceived coaching style and autocratic style was the least and there is a positive and significant relationship found between task cohesion and all leadership styles except autocratic style and social cohesion with all leadership styles except social support style. This indicates that coaches should use different leadership styles to develop their player’s team cohesion.